PENGEMBANGAN KEWIRAUSAHAAN MELALUI KOPERASI USAHA KECIL DAN MENENGAH - H. Abdul Rasul (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2016)
kewirausahaan of through co-operation and UKM is in this time viewed as by one of way of effective to yield the reliable effort hero, because through UKM development of easier effort to be developed